Community care reaches out for the mobile moment. Issue 3 (6th July 2015) - Wallace, Simon
Abstract : Purpose: – The purpose of this paper is to explore the quite extraordinary way the phenomena of mobile communication has gripped our society and the opportunities this provides for healthcare. Design/methodology/approach: – It describes the ticking public health time bomb surrounding long term conditions and dementia and the need to radically overhaul how community services are delivered. It dissects the opportunities and challenges of providing a mobile health and social care service in the community and explores what a mobile moment means for these professionals. Findings: – It stresses that the answer is NOT to simply provide an organisation's IT back-office environment in the field and describes the concept of a dedicated organisation app platform tailored to meet this need. Originality/value: – The paper concludes by reviewing recent evidence about the benefits and opportunities for health and social care organisations to embrace mobile working.